Der doppelte Odysseus. Artur Becker und die Präfigurationen durch den Mythos - Pietruszka, Przemysław (Polskie Towarzystwo Filologiczne, 2022)
The article aims to outline the reception of the Odysseus myth that occurs throughout the literary works of Artur Becker. It shows how the biography of the author and his emigration to Germany in his childhood influenced his perception of identity now understood as trans-national and cosmopolitan in its nature without the rejection of one’s heritage. Having experienced the loss of his homeland due to emigration the author identifies his fate with fellow Polish emigrants like Czesław Miłosz and Andrzej Bobkowski. From the latter he borrows the term “Kosmopolacy” which, translated to German as “Kosmopolen”, functions as a description for the identity of Becker and a trans-cultural place that he sees as his homeland after the migration. The longing for his homeland serves as an organising principle for the essays and fictional works by Becker in which the Odysseus myth prefigures the self-understanding and the works of the author, finding its pinnacle in the novel Wodka und Messer. Lied vom Ertrinken (2008). The author is a double-Odysseus for the myth is to be found both in his biography as well as his literary works.